028 Cortical sensorimotor representations remain normal in musicians' dystonia despite global deficit in dexterity. Issue 6 (27th May 2022) - Sadnicka, Anna; Wiestler, Tobias; Butler, Katherine; Edwards, Mark; Ejaz, Naveed; Diedrichsen, Jorn
Abstract : Musicians' dystonia presents with a persistent loss of motor control during musical performance. The pre- dominant hypothesis is that this loss of motor control is underpinned by maladaptive neural changes to the somatotopic organization of finger representations in primary somatosensory cortex. Here, we tested this hypothesis by investigating the finger-specific activity patterns in the primary somatosensory (S1) and motor cortex (M1) using functional magnetic resonance imaging with state-of-the art multivariate analyses in 11 musicians with dystonia and 9 healthy musicians. We also characterized their dexterous finger control to investigate whether the deficit is strictly limited to musical performance or also generalizes to a non-musical task. We report two key findings. First, during the production of individuated finger presses, musicians with dystonia showed a small, but robust loss of motor control. This deficit was characterized by both a reduction in finger individuation ability, and an exaggeration of mirror movements primarily during use of the clinically identified symptomatic hand, but also to a lesser extent during asymptomatic hand use. Second, we found no evidence of disease-related changes in the corresponding finger representa- tions in S1/M1. Our results contradict the view that abnormalities in sensorimotor finger representations play a role in the pathophysiology of musicians' dystonia. Our behavioral results also suggest that the loss of finger dexterity in musicians' dystonia expresses along a spectrum with subtle abnormalities in motor control evident during ordinary dexterous tasks. asadnick@sgul.ac.uk|ABN Bursary 39